Ethylene is involved in pistil fate by modulating the onset of ovule senescence and the GA-mediated fruit set in Arabidopsis - Carbonell Juan; Granell Antonio; Urbez Cristina; Carbonell-Bejerano Pablo; Perez-Amador Miguel A (BMC Plant Biology, 2011)
Abstract Background Ovule lifespan is an important factor in determining the ability to set fruits and produce seeds. Once ovule senescence is established, fruit set capacity in response to gibberellins (GAs) is lost. We aimed to elucidate whether ethylene plays a role in controlling ovule senescence and the fruit set response in Arabidopsis. Results Ethylene response inhibitors, silver thiosulphate (STS) and 1-methylcyclopropene (1-MCP), were able to delay the loss of pistil response to GA3. In addition, ethylene insensitive mutants ein2-5 and ein3-1 showed delayed loss of pistil response, as in plants treated with STS and 1-MCP, while constitutive mutant ctr1-1 displayed premature loss of response. The analysis of the expression of ethylene biosynthesis genes suggests that ethylene is synthesised in ovules at the onset of ovule senescence, while a transcriptional meta-analysis also supports an activated ethylene-dependent senescence upon the establishment of ovule senescence. Finally, a SAG12:GUS reporter line proved useful to monitor ovule senescence and to directly demonstrate that ethylene specifically modulates ovule senescence. Conclusions We have shown that ethylene is involved in both the control of the ovule lifespan and the determination of the pistil/fruit fate. Our data support a role of the ovule in modulating the GA response during fruit set in Arabidopsis. A possible mechanism that links the ethylene modulation of the ovule senescence and the GA3-induced fruit set response is discussed.